2003
DOI: 10.1002/app.11716
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of charge and density distributions in interfacial polymerization of thin films

Abstract: A general model for interfacial polymerization is proposed and solved numerically. The model takes into account diffusion and reaction of monomers, presence of unreacted functional groups on the growing polymer, and solubility effects. The formation of a polyamide film in composite separation membranes is taken as an example. The evolution of the concentrations of the polymer and unreacted moieties are followed explicitly, thus enabling the calculations of the limiting thickness and the asymmetric distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
125
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(142 citation statements)
references
References 19 publications
(46 reference statements)
13
125
0
Order By: Relevance
“…Freger et al presented a mathematical model for IP and investigated TEM-cross sections of membranes. They concluded that the PA-layer is heterogeneous and cannot be characterized by a single value of parameters such as charge or local polymer density [90,91]. Furthermore, they proposed that IP proceeds in three markedly different kinetic regimes.…”
Section: Interfacial Polymerizationmentioning
confidence: 99%
“…Freger et al presented a mathematical model for IP and investigated TEM-cross sections of membranes. They concluded that the PA-layer is heterogeneous and cannot be characterized by a single value of parameters such as charge or local polymer density [90,91]. Furthermore, they proposed that IP proceeds in three markedly different kinetic regimes.…”
Section: Interfacial Polymerizationmentioning
confidence: 99%
“…Some recent theoretical and simulation studies [11,12] propose an alternative mechanistic picture in which the reaction intermediates (the oligomers) diffuse away from the site of reaction, reacting with other oligomers and the monomers as they diffuse. There is no explicit phase separation leading to film formation in such mechanisms, and what can be called the 'film' is the region occupied by the oligomeric species.…”
Section: Introductionmentioning
confidence: 99%
“…In the second, the reaction is assumed to occur in a reaction zone which lies on the organic side of the interface mentioned above, and the polymer formed is excluded from the reaction zone as it forms; the reaction zone gets pushed into the organic phase as the film grows [12,13,15,17]. In the third, the reaction is assumed to occur in a steady reaction zone having a finite thickness, in which the polymer forms and accumulates (the viscosity in the zone increasing as a result), ultimately taking on a gel-like form [16]. In the first two approaches, the film thickness is explicitly calculated, increases with time and increases the diffusion resistance with time.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence [3,5,6,11,[18][19][20][21] points to a strong influence of the conditions employed in the preparation on the nature and properties of the film that forms. However, most of the models [7][8][9][10][11][14][15][16][17] focus on the kinetics and the variation of film thickness with time, and do not attempt to predict quantitatively the polymer properties as a function of process parameters. Properties such as molecular weight, polydispersity and crystallinity affect important characteristics of the polymer [20][21][22] such as mechanical properties, viscosity, ease of processing, permeability.…”
Section: Introductionmentioning
confidence: 99%